Head and Neck Cancer Diagnosis and Management of - Akarslan, Zuhre (IntechOpen, 2017)
This book includes useful and recent information to the readers regarding the following topics: Signs and symptoms and etiology and risk factors of head and neck cancer, Epidemiology and the role of microRNAs in nasopharyngeal carcinoma and oral carcinogenesis, History, classifications, and managements of salivary gland cancer, Considerations, classifications, and managements of thyroid gland cancer, Updates in the diagnosis and management of medullary thyroid carcinoma, Interventional techniques used for the relief of head and neck cancer pain, Oral side effects of head and neck irradiation, Health-related quality of life in maxillectomy patients rehabilitated with obturator prostheses